Supporting data for "Whole-genome re-sequencing of the Baikal seal and other phocid seals for a glimpse into their genetic diversity, demographic history, and phylogeny" ... - Nebenführ, Marcel; Arnason, Ulfur; Janke, Axel (GigaScience Database, 2024)
The iconic Baikal seal ( Pusa sibirica ), the smallest true seal, is a freshwater seal that is endemic to Lake Baikal where it became landlocked some million years ago. It is a rather abundant species of least concern, despite the limited habitat. Until recently, research on its genetic diversity has only been done on mitochondrial genes, restriction fragment analyses, and microsatellites, before its reference genome has been published. Here we report the genome sequences of six Baikal seals, and one individual of the Caspian seal, ringed seal, and the harbor seal, re-sequenced from Illumina paired-end short read data. Heterozygosity calculations of the six newly sequenced individuals are like the previously reported genomes. In addition, the novel genome data of the other species contributed to a more complete phocid seal phylogeny based on whole-genome data. Despite the long isolation of the land-locked Baikal seal population, the genetic diversity of this species is in the same range as other seal ...